Identification of biallelic mutations in MCM3AP and comprehensive literature analysis - Chan Liu; Qingfeng Xie; Quan Hu; Bingwu Xiang; Kaiyi Zhao; Xiang Chen; Feixia Zheng (Frontiers in Genetics, 2024)
BackgroundMinichromosome maintenance complex component 3 associated protein (MCM3AP) is a gene in which mutations can result in autosomal recessive peripheral neuropathy with or without impaired intellectual development. The MCM3AP genotype-phenotype correlation and prognosis remain unclear. The aim of this study was to explore the genotype–phenotype correlations pertaining to MCM3AP.MethodsWhole-exome sequencing (WES) combined with copy number variation sequencing (CNV-seq) were performed on the genomic DNA isolated from a Chinese family, and Sanger sequencing, quantitative PCR and cDNA analyses were performed to examine the mutations. The retrospective study was conducted on 28 individuals with biallelic MCM3AP mutation-related diseases, including features such as mutations, motor development impairment, intellectual disability, weakness/atrophy, and cerebral magnetic resonance imaging abnormalities.ResultsSequencing identified novel compound heterozygous mutations in MCM3AP, namely, a paternal variant c.1_5426del (loss of exons 1–25) and a maternal splicing variant c.1858 + 3A>G. Functional studies revealed that the variant c.1858 + 3A>G resulted in the heterozygous deletion of exon 5, thereby affecting splicing functionality. Furthermore, the compound heterozygous mutation may affect the functionality of the protein domain. Retrospective analysis revealed different genotype–phenotype correlations for the pathogenic variants in biallelic MCM3AP: all individuals (100%) with mutations outside the Sac3 domain exhibited early-onset symptoms, motor developmental delays, and cognitive abnormalities, conversely, the proportions of individuals carrying mutations within the domain were 26.7% (motor delays) and 46.7% (cognitive abnormalities).ConclusionOur findings further expand the genetic mutation spectrum of biallelic MCM3AP and highlight the genotype-phenotype associations. Additionally, we elaborate on the importance of rehabilitation intervention.